Development of Solar Powered Portable Tent for Flood Victims - Saharuddin Othman; Abdul Malik M. Ali; A.B. Zurin Zuraida (Journal of Engineering Technology, 2016)
one of the most popular renewable energy sources is solar energy. The purpose of this project is to study on renewable energy and applied at Solar Powered Portable Tent for Flood Victims. This system is designed to generate electricity to support small appliances and to reduce overall cost. The equipment uses the thin-film solar cell as a source of energy which use as a power supply in the field and which is very excellent in the maintenance, supply and does not have noise, exhaust gas and exhaust heat The equipment consists of thin-film solar cell, solar controller circuit, inverter, car battery, rice cooker and tent. The thin-film solar cell generates the power into the car battery. The solar controller is already set up with the low voltage and high voltage. If the car battery drops until 9V, the solar will charge the battery until 12V and it will automatically cut off the solar from charging the battery. The inverter then converts the DC voltage from the car battery to the AC voltage. This design applies .for electrical usage in the tent such as lighting, laptop, charge cell phones and rice cooker